Evaluation of the provision and utilization of basic public health services in Jiangsu province: a cross-sectional online survey - Lu LIAN; Dongli CAO; Siqing LI; Xiang ZHAN; Xuanxuan WANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo evaluate the provision and utilization of national basic public health services (BPHS) in Jiangsu province and to provide references for improving national basic public health service programs. MethodsUsing stratified multistage sampling and a self-designed questionnaire, we conducted an online survey in August 2022 among 1 682 employees of grassroots medical institutions (hospitals/community health centers/village clinics) and 800 residents of five groups who were key persons in need of specific health services covered by the national BPHS in three cities and three counties with different economic development in three geographical regions of Jiangsu province. Information on the provision and utilization of BPHS, and the impact of BPHS on meeting the health needs and improving the health status of the local population were collected and analyzed. ResultsValid responses were obtained from 1 408 recruited medical staff and 791 recruited residents. The most common BPHS activity for medical staff was managing resident health records (reported by 73.0% of staff), followed by health education (70.0%), managing the health of the elderly (69.2%), managing patients with hypertension (66.9%), and managing patients with type 2 diabetes (62.2%). There were significant differences in BPHS activities among primary healthcare workers in different work positions (all P<0.05). The medical staff scored all 12 BPHS items higher than 8 on a scale with a maximum score of 10 in meeting the health needs and promoting the health status of the local population. The six items with higher scores (in descending order) were preventive immunizations, health management for hypertensive patients/elderly people/patients with type 2 diabetes/children aged 0-6 years, and maternal health management; whereas the six items with lower scores (in ascending order) were health management based on traditional Chinese medicine, co-management of health and family planning regulations, management of patients with severe mental disorders, health management of tuberculosis patients, management of residents' health records, and health education. Among the five groups of key persons in need of specific health services, pregnant women reported the highest utilization of BPHS (93.8%), while lower utilization was reported by hypertensive patients (84.8%), patients with type 2 diabetes (77.1%), and the elderly (70.7%). Overall, 91.7% of key persons in need of specific health services reported satisfaction with the BPHS in improving health status, but lower proportions of the elderly (89.0%) and patients with type 2 diabetes (88.6%) reported satisfaction. ConclusionThe national BPHS generally showed good effects in improving the health status of the target population in the province. The evaluation of the delivery and utilization of the national BPHS suggests that the delivery mode and service model of the BPHS need to be optimized, and the professional capacity of grassroots health workers should be improved.